2019
DOI: 10.1002/ajmg.b.32722
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association and functional characterization of MCPH1 gene variation in bipolar disorder and schizophrenia

Abstract: A rare microcephalin 1 gene (MCPH1) variant rs61749465A>G (p.Asp61Gly) with prior evidence for association with schizophrenia (p = 3.78 × 10 −7 ) was tested for association in 2,300 bipolar disorder (BPD) participants, 1,930 SCZ participants and 1,820 normal comparison subjects. We report evidence for association of rs61749465A>G with BPD (p = 0.0009). rs61749465 is located in the N-terminal of the BRCT1 domain of MCPH1. Bioinformatic analysis predicted the Asp61Gly substitution to be damaging to MCPH1 functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For instance, more pronounced transcriptome alterations in pathways involved in protein synthesis and translation initiation in the dorsolateral prefrontal cortex pyramidal cells were associated with the diagnosis of SCZ in human brain specimens obtained during biopsies [21]. Additionally, functional analyses (including metabolic activity, DNA damage repair and mRNA stability assays) suggested that a microcephalin (MCPH1) gene variant with a potential impact on protein translation is associated with the risk of SCZ [22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, more pronounced transcriptome alterations in pathways involved in protein synthesis and translation initiation in the dorsolateral prefrontal cortex pyramidal cells were associated with the diagnosis of SCZ in human brain specimens obtained during biopsies [21]. Additionally, functional analyses (including metabolic activity, DNA damage repair and mRNA stability assays) suggested that a microcephalin (MCPH1) gene variant with a potential impact on protein translation is associated with the risk of SCZ [22].…”
Section: Introductionmentioning
confidence: 99%
“…Again, in a clinical situation any potentially pathogenic variants would need to be confirmed by Sanger sequencing. The observation of a subject homozygous for a probably damaging variant in MCPH1, a gene in which recessively acting variants can cause microcephaly, is possibly of some interest because of reports of variants in this gene being associated with schizophrenia and bipolar disorder (42)(43)(44). However the effects of this particular variant are too uncertain for this finding to have any value in a clinical context.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesising that novel CDS might harbour previously undetected pathogenic variants, we integrated our novel transcript annotations with sequencing data from patients with neurodevelopmental phenotypes. First we used published exome sequencing data 30 from psychosis patients (n = 1,551 schizophrenia and 1,949 bipolar disorder) and 1,117 controls 25,31 (see Methods ). Although these data are limited by the coverage of exome sequencing which does not capture any novel exons, there was an overall significant enrichment of rare (gnomADv2 MAF<1×10 -4 ) non-synonymous damaging variants in novel CDS captured by exome-seq in patients (OR = 2.8, P = 0.02, Fig.…”
Section: Mainmentioning
confidence: 99%